Mixue are Everywhere: Prosumerism on Users Content Production in Tiktok - Tangguh Okta Wibowo; Khairul Syafuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Mixue is a franchise that is well-known for selling beverages and ice cream. Mixue's viral material on social media, like Tiktok, makes it easy to recognize the popularity of the Mixue’s products. This research intends to examine prosumers involved in audio-visual content development who contribute to the marketing of Mixue brand. This research uses interpretative content analysis to examine audio-visual contents created by Tiktok users. The results of the study indicate that videos created by Tiktok users acting as prosumers have a role in the reproduction of diverse values on their experience with Mixue items. The circulation of their videos on Tiktok increases the exposure of the Mixue brand. These scattered videos show various types of performances with different video production techniques and stories. These findings illustrate the intensification of information produced and communication that has been built through the role of Tiktok, which spreads very quickly. This shows that prosumers reproduce videos based on their respective consumer behavior through the creative side of the actors as consumers